Development and evaluation of novel artemisinin-isatin hybrids with potential anti-leukemic cytotoxicity - Wang, Peng; Zhang, Zhe; Cao, Wei; Zhang, Xuan (Frontiers in Oncology, 2023)
Twenty-one novel ester tethered artemisinin-isatin hybrids were designed, synthesized and screened against human myeloid leukemia cell lines (K562 and K562/ADR), human acute lymphoblastic leukemia cell line (CCRF-CEM) as well as normal human peripheral blood mononuclear cells (PBMCs) for their cytotoxicity by MTT assay. The structure-activity relationships (SARs) were also discussed to facilitate further rational design of more effective candidates. The preliminary results showed that most of the ester tethered artemisinin-isatin hybrids (IC50: 0.32-29.35 µM) exhibited promising activity against CCRF-CEM cells, and some of them (IC50: 1.23-49.84 µM) were also active against K562 and K562/ADR human myeloid leukemia cell lines. Among them, hybrid 7d (IC50: 0.32, 2.67 and 1.23 µM) not only possessed profound activity against the three tested leukemia cell lines and excellent safety and selectivity profiles, but also showed promising pharmacokinetic properties. Accordingly, hybrid 7d could be considered as potential lead molecules for the development of novel anti-leukemic agents with minimal untoward events to normal human cells.